2009
DOI: 10.1177/000312240907400503
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Class Inequality in Higher Education

Abstract: This study develops a comprehensive theoretical framework regarding the evolution of the class divide in postsecondary education. I conceptualize three prototypes of class inequality—effectively maintained, declining, and expanding—and associate their emergence with the level of competition in college admissions. I also unearth the twin mechanisms, exclusion and adaptation, that link class hierarchy to a highly stratified postsecondary system in an allegedly meritocratic environment. Intra- and inter-cohort co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
238
0
20

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 300 publications
(279 citation statements)
references
References 52 publications
(69 reference statements)
10
238
0
20
Order By: Relevance
“…This research has increased over the most recent 15 years along with the sheer number of post-secondary institutions and, therefore, the number of students receiving undergraduate degrees. However, these increases do not appear to have correlated to increased access for students of low SES into moderately selective or very selective institutions (Alon, 2009;Davis, 2003;Davis, Bauman & USCB, 2013;Karen, 2002;Kim, 2010;Shavit, Arum, Gamoran, & Menachem, 2007). The increased access, which students of low SES have seen over this period, has mostly come through community college expansion and by increased enrollments in for-profit institutions (Davis et al, 2013;Dougherty & Kienzl, 2006;Shavit et al, 2007).…”
Section: Significance Of the Problemmentioning
confidence: 99%
See 4 more Smart Citations
“…This research has increased over the most recent 15 years along with the sheer number of post-secondary institutions and, therefore, the number of students receiving undergraduate degrees. However, these increases do not appear to have correlated to increased access for students of low SES into moderately selective or very selective institutions (Alon, 2009;Davis, 2003;Davis, Bauman & USCB, 2013;Karen, 2002;Kim, 2010;Shavit, Arum, Gamoran, & Menachem, 2007). The increased access, which students of low SES have seen over this period, has mostly come through community college expansion and by increased enrollments in for-profit institutions (Davis et al, 2013;Dougherty & Kienzl, 2006;Shavit et al, 2007).…”
Section: Significance Of the Problemmentioning
confidence: 99%
“…These studies suggested that it was getting harder for low SES students to enroll in selective higher education as a whole, and that the institution of higher education in the United States was becoming further stratified despite the high degree of total national enrollment in postsecondary educational programs (Alon, 2009;Baum, Ma, & College Board Advocacy & Policy Center, 2011;Curs, 2008;Davis, 2003;Davis et al, 2013;Haveman & Smeeding, 2006;Kim, 2010). This study intended to investigate a selective, high cost of attendance institution where approximately 25% of the annual incoming freshmen class was Pell Grant eligible.…”
Section: Barriers To Low Ses Student Enrollmentmentioning
confidence: 99%
See 3 more Smart Citations